PROBLEMS OF RECONSTRUCTION AND RENOVATION OF THE CURRENT DEVELOPMENT - Omonova Dilnoza Fayziddinovna (Scholar Express Journal, 2022)
The article deals with the actual problems of reconstruction and renovation of the existing buildings. The main provisions, goals and objectives of the renovation of the housing stock are analyzed. Some aspects of solving the housing problem are highlighted
Keywords: reconstruction; renovation; residential development; housing stock